Cytologic Analysis of Epstein-Barr Virus-Associated T/Natural Killer-Cell Lymphoproliferative Diseases - Yachie, Akihiro (Frontiers in Pediatrics, 2018)
Rapid, precise diagnosis of Epstein-Barr virus-associated T lymphocyte or natural killer cell lymphoproliferative diseases is clinically important to prevent disease progression and avoid fatal outcomes for patients. In addition to detecting increased copy numbers of Epstein-Barr virus, identification of the lymphocyte subpopulation targeted by the virus infection is crucial to reaching the final diagnosis. However, these procedures are laborious and require large amounts of sample. In contrast, flowcytometric analysis may provide crucial information for initial screening of diseases using only small amounts of sample and involves little labor. In addition to the increase of a particular subpopulation, selective HLA-DR expression indicates selective activation and expansion of a virus-infected clone. Presence of a characteristic HLA-DRhigh CD5dim/negative fraction within CD8+ T lymphocytes indicates a possible diagnosis of Epstein-Barr virus-associated hemophagocytic lymphohistiocytosis. One should note, however, that cases with familial hemophagocytic lymphohistiocytosis may exhibit a similar abnormal fraction within CD8+ T lymphocytes. These T cells are oligoclonally expanded reactive T cells expanding in response to B cells infected with Epstein-Barr virus.